Study on Factors Affecting Cavitation Effect in Venturi Tube - SHAO Jun peng; LIU Ya nan (Journal of Harbin University of Science and Technology)
The dynamic cavitation model of airwater twophase flow was established according to the time variation of air precipitation and digestion process in water, which was used in FLUENT threedimension numerical simulation to simulate the airwater twophase flow, and the variation law of venturi tube throat diameter、inlet pressure and tandem venturi on vapor volume fraction were obtained The results of numerical simulation and experiments show that the vapor volume fraction increases with pressure increasing，But not infinitely increasing, there are limits;As the throat diameter increases, the cavitation effect of the venturi tube gradually decreases;Under the same conditions, the cavitation effect of the tandem venturi is not as good as the cavitation effect of a single venturi, that is, the twostage cavitation cannot be realized by the tandem venturiThe above research is of great significance to the engineering application of venturi tubes